Recoverable autonomous sonde for subglacial lake exploration: electronic control system design. Issue 85 (18th September 2021) - Peng, Shilin; Jiang, Xiao; Tang, Yongzhen; Li, Chong; Li, Xiaodong; Huang, Shengmiao; Zhu, Tianxin; Shi, Jianguang; Sun, Youhong; Talalay, Pavel; Fan, Xiaopeng; Zhang, Nan; et al.
Abstract: Subglacial lake exploration is of great interest to the science community. RECoverable Autonomous Sonde (RECAS) provides an exploration tool to measure and sample subglacial lake environments while the subglacial lake remains isolated from the glacier surface and atmosphere. This paper presents an electronic control system design of 200 m prototype of RECAS. The proposed electronic control system consists of a surface system, a downhole control system, and a power transfer and communication system. The downhole control system is the core element of RECAS, and is responsible for sonde status monitoring, sonde motion control, subglacial water sampling and in situ analysis. A custom RS485 temperature sensor was developed to cater for the limited size and depth requirements of the system. We adopted a humidity-based measurement to monitor for a housing leak. This condition is because standard leak detection monitoring of water conductivity may be inapplicable to pure ice in Antarctica. A water sampler control board was designed to control the samplers and monitor the on/off state. A high-definition camera system with built-in storage and self-heating ability was designed to perform the video recording in the subglacial lake. The proposed electronic control system is proven effective after a series of tests.